2008
DOI: 10.1111/j.1467-9566.2008.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Making monsters: heterosexuality, crime and race in recent Western media coverage of HIV

Abstract: In the early HIV epidemic, Western media coverage encouraged the idea that infection was linked to ‘other’ identities located outside the ‘mainstream’; outside ‘proper’ heterosexuality. Today, however, HIV has become repositioned as a global heterosexual epidemic. Analyses show that since the 1990s Western media have shifted away from blame and hysteria to an increasingly routinised reporting of HIV as a health story and social justice issue. But recent years have seen the emergence of a new media story in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 35 publications
0
77
0
2
Order By: Relevance
“…24 Several studies, in fact, have highlighted a shift away from the reporting of the 1980s and 90s, when HIV/AIDS was often referred to as the 'gay plague' and reports focussed on domestic tales of homosexuals and drug users, 15,25,26 to HIV/AIDS as a 'global epidemic', particularly affecting heterosexuals in Africa. 27 Although this is somewhat reflected in our analysis, it fails to reflect the current epidemiology of HIV in the UK 28 and has implications for prevention if those at highest risk (i.e. men who have sex with men) are distanced from perceptions of risk.…”
Section: Discussionmentioning
confidence: 78%
“…24 Several studies, in fact, have highlighted a shift away from the reporting of the 1980s and 90s, when HIV/AIDS was often referred to as the 'gay plague' and reports focussed on domestic tales of homosexuals and drug users, 15,25,26 to HIV/AIDS as a 'global epidemic', particularly affecting heterosexuals in Africa. 27 Although this is somewhat reflected in our analysis, it fails to reflect the current epidemiology of HIV in the UK 28 and has implications for prevention if those at highest risk (i.e. men who have sex with men) are distanced from perceptions of risk.…”
Section: Discussionmentioning
confidence: 78%
“…HIV programs for the general community have been subsumed within broader prevention campaigns where the focus is largely on other STIs, given the significantly higher prevalence of STIs among heterosexuals compared with HIV, but these campaigns have been targeted primarily at young people (Commonwealth of Australia, 2010). One unintended consequence of this is that HIV has become culturally coded and socially invisibilized in heterosexual society as a disease that mainly affects gay men, whilst heterosexuality has become inscribed as safe and as exempt from risk (Persson & Newman, 2008). The scant research available on HIV-positive heterosexuals in Australia shows that they were largely oblivious to HIV prior to their diagnosis, or else did not consider HIV as personally relevant and, therefore, HIV rarely figured as a concern in their sexual practices (Down et al, 2012;Persson, Barton, & Richards, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although not the focus of this article, this is a complex issue that is clearly implicated in partner selection and online dating that deserves further exploration in relation to the enactment of both 'African' masculinity and femininity in the HIV field; echoing media portrayals of 'monstrous' African masculinity in relation to criminal prosecutions of HIV infection (Persson and Newman, 2008) and the broader, much criticised, stereotype of the 'promiscuous black African male' (Doyal et al, , p. 1904). …”
Section: Viral-sociality: Mutual Responsibility and Sharing The Virusmentioning
confidence: 96%
“…Although not a common occurrence, there have been a number of such prosecutions in the United Kingdom (Weait, 2007;Dodds et al, 2009), with these cases receiving widespread media attention, in which the people living with HIV in question have often been brutally demonised (Persson and Newman, 2008). It has been suggested that one of the reasons HIV-positive gay man prefer meeting partners online is because they find it easier to disclose over the internet and in doing so avoid the risk of criminalisation (Dodds et al, 2009).…”
Section: 'It's Your Decision': Disclosing An Hiv-positive Statusmentioning
confidence: 98%